The surgical management of heart failure: heart transplantation in the era of SARS-CoV-2 pandemic. (14th October 2021) - Malyszek, J; Jasinska, M; Zembala, M; Ratman, K; Krol, B; Tkocz, K; Pelar, K; Sybila, P; Pajor, M; Nawrat, Z
Abstract: Purpose: End-stage heart failure (HF) is a major global clinical problem with a growing number of patients worldwide. Heart transplantation (HTx) and mechanical circulatory support (MCS) represent the two most effective procedural options for the treatment of end-stage HF. HTx remains the treatment of choice in patients who reach maximal medical therapy, but, remain incapacitated by their symptoms. The COVID-19 pandemic caused by SARS-CoV-2 has significantly affected the delivery of medical care across all specialties, therefore, it is not a surprise that the number of HTx has drastically diminished worldwide during the pandemic. We developed in our Center of Heart Diseases effective safety measures and team approach in order to perform HTx with excellent outcomes. Methods: All patients with reduced ejection fraction, heart failure at presentation and had been adequately investigated had been evaluated by a multidisciplinary team and when appropriate entered into a waiting list for HTx. Results: From March2020 to March 2021, 96 patients underwent orthotopic HTx. The age range was 33 - 66 yrs and a median of 54 yr. Both donor and recipient were tested for SARS-CoV-2 within 48 hrs of the procedure, and none tested positive. All recipients were regularly tested following the procedure, too, and none were positive. 53 patients with INTERMACS 4 class have been treated, 31 with INTERMACS 3 class and 11 patients with INTERMACS 2. Only one patient with INTERMACS 1 underwent HTx. 6 (10%) patients died within the first 30 days following HTx. All staff caring for those patients were screened for SARS-CoV-2 at regular intervals. There was liberal use of PPE at all stages of the care of the patients, with strict hand hygiene. All surviving patients were subjected to the normal protocol of post-operative management in terms of immunosuppression and other medications. Conclusion: Heart transplantation remains the treatment of choice for advanced heart failure. About 85% of heart transplant patients survive one year following the procedure thus giving them a better quality of life. We have shown that successful heart transplantation may be performed during the SARS-CoV-2 pandemic. FUNDunding Acknowledgement: Type of funding sources: None.